The Mirror of Literature, Amusement, and Instruction. Volume 10, No. 268, August 11, 1827 - Various (Salt Lake City, UT : Project Gutenberg, 2003)
"The Mirror of Literature, Amusement, and Instruction. Volume 10, No. 268,$1! =(B" is a periodical publication from the early 19th century, specifically dating back to 1827. This literary magazine serves as a collection of essays, articles, poetry, and illustrations that aim to entertain and educate its readers. The topics often range from historical accounts and cultural commentary to medical lectures and ethical discussions, reflecting the varied interests of its audience during the early Victorian era. The contents of this particular volume include a detailed exploration of the history of the Hospital of St. Thomas in Canterbury, discussing its significance as a resting place for pilgrims and its evolution over the years. Additionally, the volume features medical insights into minor affections of the brain, hydrophobia, and the importance of kindness towards the sick, underscoring the connection between emotional support and recovery. Literary elements, such as the poem "The Months," celebrate seasonal changes and agricultural life, while articles reflect on contemporary issues and notable historical figures. Overall, the publication weaves together literature with instruction, providing both amusement and informative content for its readers. (This is an automatically generated summary.)s
Release date is 2003-10-09
E-text prepared by Jonathan Ingram and Project Gutenberg Distributed Proofreaders
Keywords: Popular literature -- Great Britain -- Periodicals